Eksistensi Inklusi Keuangan Dalam Perkembangan UMKM Tenun Ikat, Kecamatan Nita, Kabupaten Sikka - Christina Natalia; Cicilia A. Tungga; Nikson Tameno (Moneter : Jurnal Ekonomi dan Keuangan, 2024)
This research aims to determine the role of financial inclusion in increasing the income of ikat weaving MSMEs in the sub-district, determine the role of financial inclusion in the development of ikat weaving MSMEs in Nita sub-district and find out what factors hinder the management of economic potential and development of ikat-weaving MSMEs in Nita sub-district. The research used is a case study. The research approach used is descriptive qualitative. The data sources used are primary data and secondary data, where data collection uses observation, interview and documentation study techniques. The data analysis techniques used are data reduction, data display, and conclusions. The results of the research show that the economic potential that can be managed and which is most prominent in Nita sub-district is the tourism potential in the form of ikat weaving. Efforts made by ikat weaving businesses to reduce unemployment are by opening employment opportunities for people who have skills in weaving.